SAFE DEVICE FOR INTRAHOSPITAL TRANSPORTATION OF NEWBORNS AND THEIR MOTHERS: EVALUATION AND USABILITY - Thomaz Abramsson Gonçalves; Helga Geremias Gouveia; Marcia Simone de Araújo Machado Siebert; Marianna Goes Moraes (Universidade Federal do Paraná, 2020)
Objective: To evaluate the usability of the baby carrier for the safe transport of newborn infants with their mothers and the satisfaction of the mothers and the nursing team. Method: Cross-sectional study conducted at the Obstetric Center and Inpatient Obstetric Units, in the southern region of Brazil, with 99 postpartum women and 66 nursing technicians/ assistants from July to September 2018. Three semi-structured questionnaires were applied. Descriptive analysis was performed. Results: Of the total number of nursing technicians/assistants, 40 were from the Obstetric Center and 23 from the Inpatient Obstetric Units. Ninety-five (95) postpartum women 95 perceived the device as a safety measure for the newborns. As for satisfaction, the average score of the nursing team at the Obstetric Center was 8.9; in Obstetric Admission, 9.6; and, the postpartum women obtained 9.6. Conclusion: The use of the baby carrier obtained high ratings from the professionals and the mothers, because it prevented falls of newborns during transport. Suggestions for improvements of the device should be considered.